Treatment of Dairy Industry Wastewater - Special Reference to Design of Aerated Lagoon - Kamble, Sheetal; Bhargava, Akshey; Patil, Purvi (Journal of Water, 2020)
Industrial revolution brought diversified industries to produce goods to meet the demand of increasing population. Such a rapid growth of industrial sector caused water pollution to a great extent. Dairy industry is not an exception, causing significant water pollution. The dairy sector in India grew at a rate of 6.4 per cent annually in the last four years against the global growth rate 1.7 per cent demonstrating significant increase in milk productivity. Around 80 million rural Indian households are engaged in milk production with very high proportion being landless, small and marginal farmers. But on the other hand, water pollution being caused from these dairy industries is quite significant. Various biological treatment technologies were tried for treating dairy wastewater. An attempt has been made by the authors of the present paper to design aerated lagoon including screen chamber, primary clarifier, quiescent settling zone and sludge disposal with success to treat dairy wastewater.
Keywords: Dairy wastewater; characteristics; treatment methods; aerated lagoon design; treated waste water applications.